Play Support Strategies of Preschool Teachers with Different Perspectives on Play and Its Role in Child’s Development - A.N. Iakshina; T.N. Le-van (Культурно-историческая психология, 2023)
The recognition of play importance does not always lead to the creation of good conditions for its development. An attempt to turn play into classes, to use it for teaching, leads to the disappearance of spontaneous play from kindergartens. There is a gap between the declared pedagogical aim and real practice. This may be due to understanding the key features of play and its role in child’s development. The purpose of the study is to study what criteria teachers use to distinguish between play and a pseudo-play, how the understanding of play is related to the strategy of its support. Structured interviews, including commentary on 2 videos, were conducted with 34 preschool teachers. The assessment of the conditions for play development was carried out using the scale "Play Environmental Rating Scale" in 28 preschool classrooms (13 kindergartens). The average total score is 3,35 (sd=1,31; med=3,43), which corresponds to the minimal quality level of conditions for play. Key deficits are the participation of the teacher in joint play with children, the provision of conditions for multi-age interaction. Significant differences are revealed in the strategy of play support among teachers with a contrasting understanding of the pseudo-play video. Teachers who distinguish between play and pseudo-play and emphasize the developmental value of spontaneous children's play create a multifunctional play environment and more often participate in joint play as partners. Teachers who do not distinguish between a play and a pseudo-play are more often too didactic or outsiders, they create a realistic play environment. The results of the study can be used in elaboration of programs for teacher’s professional development.